2014
DOI: 10.1111/and.12219
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical presentation of Klinefelter's syndrome in monozygotic twins

Abstract: There is a wide variability in the clinical presentation of Klinefelter's syndrome. We report the case of a 45-year-old man who was incidentally diagnosed a 47,XXY/46,XY karyotype in a bone marrow aspiration (case 1). He presented hypogonadic features with undetectable testosterone levels and a height in accordance with mid-parental height. He had a monozygous sibling (case 2) who did not show clinical signs of hypogonadism and whose height exceeded mid-parental height. Both patients had presented language dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…17 Overexpression of the SHOX gene is likely to be responsible for the normal stature seen in patients with KS. 18,19 No definite pathogenic mutation was found in the patient's SHOX sequence.…”
Section: Discussionmentioning
confidence: 92%
“…17 Overexpression of the SHOX gene is likely to be responsible for the normal stature seen in patients with KS. 18,19 No definite pathogenic mutation was found in the patient's SHOX sequence.…”
Section: Discussionmentioning
confidence: 92%
“…Somatic mosaicism, a type of genetic mosaicism, is one of the causes of genetic disorders that the peripheral chromosomal test does not detect. Benaiges et al (2015) reported monozygotic twins with KS with 46, XY/47, XXY who showed different physical features. They identified the ratio of testicular tissue affected by mosaicism to be a possible reason for the difference.…”
Section: Discussionmentioning
confidence: 99%
“…Najčastejšími dôvodmi vedúcimi k diagnóze sú najmä infertilita a malé testes. Ďalšie príznaky, ktoré môžu byť prítomné sú vysoká postava, gyneko mastia, prejavy hypoandrogenizácie, oneskorená puberta, problémy s učením [2]. Laboratórnym nálezom pri KS je hypergonadotropný hypogonadizmus s vyššou hladinou FSH ako LH.…”
Section: úVodunclassified